Complement in Non-Antibody-Mediated Kidney Diseases - Angeletti, Andrea; Reyes-Bahamonde, Joselyn; Cravedi, Paolo; Campbell, Kirk N. (Frontiers in Medicine, 2017)
ABSTRACT The complement system is part of the innate immune response that plays important roles in protecting the host from foreign pathogens. The complement components and relative fragments deposition have long been recognized to be strongly involved also in the pathogenesis of autoantibody-related kidney glomerulopathies, leading to direct glomerular injury and recruitment of infiltrating inflammation pathways. More recently, unregulated complement activation has been shown to be associated with progression of non antibody-mediated kidney diseases, including focal segmental glomerulosclerosis, C3 glomerular disease, trombotic microangiopathies or general fibrosis generation in progressive chronic kidney diseases. Some of the specific mechanisms associated with complement activation in these diseases were recently clarified, showing a dominant role of alternative activation pathway. Over the last decade, a growing number of anti-complement agents have been developed and some of them are being approved for clinical use or already in use. Therefore, anti-complement therapies represent a realistic choice of therapeutic approaches for complement-related diseases. Herein, we review the complement system activation, and regulatiry mechanisms, their involvement in non-antibody mediated glomerular diseases and the recent advances in complement-targeting agents as potential therapeutic strategies.